2016
DOI: 10.1099/mgen.0.000088
|View full text |Cite
|
Sign up to set email alerts
|

Monomorphic genotypes within a generalist lineage of Campylobacter jejuni show signs of global dispersion

Abstract: The decreased costs of genome sequencing have increased the capability to apply whole-genome sequencing to epidemiological surveillance of zoonotic Campylobacter jejuni. However, knowledge of the genetic diversity of this bacteria is vital for inferring relatedness between epidemiologically linked isolates and a necessary prerequisite for correct application of this methodology. To address this issue in C. jejuni we investigated the spatial and temporal signals in the genomes of a major clonal complex and gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 67 publications
(94 reference statements)
2
27
0
Order By: Relevance
“…In contrast to raccoon-adapted clades, 78% of isolates in clade B, which contained approximately 30% of raccoon isolates in this study, were from subtypes with mixed-host association. Mixed-source genotypes have been well-described and typically include representatives from Clonal Complexes (CCs) described as 'generalists' including ST-45, ST-21, and ST-48 (52)(53)(54)(55). These CCs are highly prevalent worldwide, known for their broad host distribution, including livestock, and high burden of human illness.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to raccoon-adapted clades, 78% of isolates in clade B, which contained approximately 30% of raccoon isolates in this study, were from subtypes with mixed-host association. Mixed-source genotypes have been well-described and typically include representatives from Clonal Complexes (CCs) described as 'generalists' including ST-45, ST-21, and ST-48 (52)(53)(54)(55). These CCs are highly prevalent worldwide, known for their broad host distribution, including livestock, and high burden of human illness.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up publication, Llarena et al investigated the nature of the population structure of ST-45 clonal complex (CC), focusing on identifying a possible spatial-temporal evolutionary signal. The authors found that the occurrence and strength of the geographical signal varied between sublineages of ST-45 CC strains, but they could not find evidence of a temporal signal (6). In addition, the authors unexpectedly identified certain sublineages of ST-45 with extremely similar genomes regardless of the time and location of sampling.…”
Section: Defining the Baseline Genomic Diversity Of C Jejunimentioning
confidence: 94%
“…In addition, the authors unexpectedly identified certain sublineages of ST-45 with extremely similar genomes regardless of the time and location of sampling. These successful monomorphic clones were persistently isolated from animal hosts and human patients over a decade, from several countries around the world (6). There is no reason to think that clonal dispersal is limited to certain sublineages of ST-45.…”
Section: Defining the Baseline Genomic Diversity Of C Jejunimentioning
confidence: 99%
“…Multilocus sequence typing (MLST) has been an invaluable molecular typing method, providing essential knowledge about C. jejuni types occurring in various hosts and sources worldwide. MLST is, however, limited to the characterization and discrimination of isolates according to sequence type (ST) (11)(12)(13); thus, more accurate methods, such as whole-genome MLST (wgMLST), are increasingly being used (11,14) to compare genetically related isolates in more detail and to be able to identify clones potentially originating from the same source. In previous studies, most of the STs found among wild birds, including mallard ducks (5), barnacle geese (7), starlings (15), and several other bird species (16), have been considered to represent mainly hostassociated STs, differing from those STs reported in human patients or domestic animals.…”
mentioning
confidence: 99%